2008
DOI: 10.1111/j.1755-5922.2008.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Nebivolol: A Highly Selective β1‐Adrenergic Receptor Blocker That Causes Vasodilation by Increasing Nitric Oxide

Abstract: Nebivolol (Bystolic R ) is a cardioselective beta 1 (β 1 )-adrenergic receptor blocker with endothelium-dependent vasodilating properties. The endothelium-dependent relaxation induced by nebivolol is blocked by inhibitors of nitric oxide synthase (NOS) and guanylate cyclase. Nebivolol also increases in vitro and in vivo nitric oxide (NO), which is an essential signaling molecule involved in the maintenance of cardiovascular homeostasis. This review summarizes the data involving nebivolol and NO bioavailability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
1
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 63 publications
2
85
1
7
Order By: Relevance
“…In addition, nebivolol also increases . NO release from the endothelium, thus attenuating oxidative stress effects on endothelium-dependent vasodilation [309,310]. The calcium channel blocker lacidipine has also been demonstrated…”
Section: Antihypertensive Treatments With Direct and Indirect Antioximentioning
confidence: 99%
“…In addition, nebivolol also increases . NO release from the endothelium, thus attenuating oxidative stress effects on endothelium-dependent vasodilation [309,310]. The calcium channel blocker lacidipine has also been demonstrated…”
Section: Antihypertensive Treatments With Direct and Indirect Antioximentioning
confidence: 99%
“…It is unique among all β1-adrenoceptor blockers in that it possesses a vasodilatory property attributed to synthesis of NO [21,22] as well as to increasing NO bioavailability by decreasing the oxidative stress [23][24][25][26][27]. The observation that nebivolol increases the concentration of nitrite in 7 out of 10 as-says using different doses and at different time intervals, reflecting an increase in the NO levels, is confirmatory to observations reported by others [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…It is unique among all β1-adrenoceptor blockers in that it possesses a vasodilatory property attributed to synthesis of NO [20,21] as well as to increasing NO bioavailability by decreasing the oxidative stress [22][23][24][25][26]. In addition, Ladage et al [27] reported that the endothelium-dependent increase in NO induced by nebivolol was due to stimulation of β 3 -adrenoceptors and estrogen receptors.…”
Section: Introductionmentioning
confidence: 99%
“…The latest generation of β-blockers commonly possesses some additional beneficial features that can improve their therapeutic profile and reduce their sometimes serious side effects. These features are mainly antioxidant properties (e.g., carvedilol [3]), vasodilatory activity (e.g., carvedilol, nebivolol [3,4]) and ultra-short effect (e.g., esmolol, landiolol [5,6]). …”
Section: Introductionmentioning
confidence: 99%
“…The cardiovascular activity of the discussed compounds is provided by the presence of the arylcarbonyloxyaminopropanol pharmacophore (β-adrenolytic activity; the ester moiety ensures ultra-short effect) and the phenylpiperazine fragment (α 1 -adrenolytic activity) [2,8]. The arylcarbonyloxyaminopropanol scaffold is formed by the benzene ring (as a part of 4-hydroxybenzoic acid) substituted at the C (4) position with a propoxy chain. The phenylpiperazine segment, the basic part of the molecule, is either unsubstituted or substituted with a methoxy or a fluoro moiety in the C (2) 1 or C (4) 1 position.…”
Section: Introductionmentioning
confidence: 99%